Intellectual capital and maintenance of work ability: The wellbeing perspective - Tomi Hussi (The Research Institute of the Finnish Economy (ETLA), 2003)
The well-being perspective of the employees' is only seldom connected to the discussion on intellectual capital. This paper analyses expert interview data on intellectual capital with maintenance of work ability (MWA) as frame of reference. The framework includes employees' health but also competencies, work community and work environment. This paper shows that the most essential change caused by intellectual capital has taken place in relation to competence because the focus is shifting from individual's competencies to collective competence. Changes in work environment, work community and employee's health are shown to be underlying processes behind this development. Employees' wellbeing, which is the prerequisite for successful knowledge creation, is determined by successful management of all these four processes. – – Työntekijöiden hyvinvointiin liittyviä kysymyksiä ei juurikaan ole tarkasteltu osaamispääomaan liittyvän keskustelun yhteydessä. Tässä paperissa analysoidaan osaamispääoman asiantuntijoista koostuvaa haastatteluaineistoa työkykyä ylläpitävää toimintaa (tyky) viitekehyksenä käyttäen. Tyky-viitekehys sisältää työntekijöiden terveyden lisäksi myös osaamisen, työyhteisön ja työympäristön näkökulmat. Tässä paperissa keskeisimmäksi osaamispääoman aiheuttamaksi muutokseksi osoittautuu osaaminen, jossa painopiste on siirtymässä yksilöiden osaamisesta yhteisölliseen osaamiseen. Muutokset työympäristöön, työyhteisöön ja työntekijöiden terveyteen liittyvissä kysymyksissä jäsentävät tämän kehityksen taustalla vaikuttavia tekijöitä. Työntekijöiden hyvinvointi, joka on onnistuneen tiedonmuodostuksen perusedellytys, määrittyy kaikkien näiden neljän tekijän menestyksellisestä hallinnasta. – osaamispääoma ; työkykyä ylläpitävä toiminta ; työntekijöiden hyvinvointi ; tiedonmuodostus ; kestävä tuloskehitys ; terveys ; kompetenssi ; työyhteisö ; työympäristö
Keywords: 330; intellectual capital; maintenance of work ability; employees' wellbeing; knowledge creation; sustainable economical development; health; competence; work community; work environment; Kompetenz; Innovationsmanagement; Wissensmanagement